PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER DENGAN METODE MULTIKOMUNIKASI UNTUK SISWA KELAS IV SDLB PENYANDANG TUNA RUNGU DAN WICARA - Agus Salim (Jurnal Techno Nusa Mandiri, 2015)
A deaf person is an individual who has a hearing impediment in both permanent and not permanent. In each teaching for deaf children, teaching aids needed to visualize the material presented, making it easier to understand. Mathematics learning models can be appropriate tools in teaching math to deaf children. This learning model is intended for students in 4th grade of SDLB B. This application presents mathematics material that is explained using animations, pictures, text, and videos. By using this application, teaching and learning activities become more enjoyable and can shorten the time of teaching. The research shows that deaf person more focused on his learning material comparing with conventional teaching. This method makes people learn 40% faster than the conventional method.